1998
DOI: 10.1016/s0735-1097(97)00443-9
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Calcification and Not Lumen Stenosis Is Highly Correlated With Atherosclerotic Plaque Burden in Humans: A Histologic Study of 723 Coronary Artery Segments Using Nondecalcifying Methodology

Abstract: Coronary calcium quantification is an excellent method of assessing atherosclerotic plaque presence at individual artery sites. Moreover, the amount of calcium correlates with the overall magnitude of atherosclerotic plaque burden. This study suggests that the remodeling phenomenon is the likely explanation for the lack of a good predictive value between lumen narrowing and quantification of mural calcification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
471
0
18

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 924 publications
(511 citation statements)
references
References 37 publications
22
471
0
18
Order By: Relevance
“…This concept has been subsequently highlighted with the use of non-contrast coronary CT (16), and in the histologic analysis of coronary artery segments (17). In the latter study, CAC quantification was an excellent predictor of coronary artery plaque burden within each coronary artery (left anterior descending coronary artery: r=0.89, p < 0.0001; left circumflex coronary artery: r=0.7, p < 0.001; right coronary artery: r=0.89, p < 0.0001).…”
Section: Regional Cac Measures and Correlation With Coronary Atheroscmentioning
confidence: 99%
“…This concept has been subsequently highlighted with the use of non-contrast coronary CT (16), and in the histologic analysis of coronary artery segments (17). In the latter study, CAC quantification was an excellent predictor of coronary artery plaque burden within each coronary artery (left anterior descending coronary artery: r=0.89, p < 0.0001; left circumflex coronary artery: r=0.7, p < 0.001; right coronary artery: r=0.89, p < 0.0001).…”
Section: Regional Cac Measures and Correlation With Coronary Atheroscmentioning
confidence: 99%
“…Very low HU value in the plaque (\0 HU) are associated with the presence of intraplaque haemorrhage [53,54]. The presence of fatty plaques are associated with an increase risk of stroke [55], whereas the presence of calcium in the carotid artery plaques seems to be a protective factor [18,56], which is unlike the coronary arteries [57,58]. It is hypothesized that calcium in the carotid atheromatous plaques confers stability, resulting in a protection against the biomechanical stress and the disruption.…”
Section: The Plaque Compositionmentioning
confidence: 99%
“…However, the introduction of new techniques to measure vascular calcification noninvasively, such as electron beam computed tomography, have revolutionized our current thinking about the risks of vascular calcification. In coronary arteries, calcification is positively correlated with atherosclerotic plaque burden (11,12), increased risk of myocardial infarction (13)(14)(15), and plaque instability (2,16). Although some of these findings may relate to the correlation of coronary calcification with extent of underlying atherosclerotic disease, it is also possible that vascular calcification itself may contribute to initiation or progression of cardiovascular disease (CVD).…”
Section: Clinical Consequences Of Vascular Calcificationmentioning
confidence: 99%
“…(53). Indeed, when sevelamer was compared to commonly used Ca-based P binders in a large hemodialysis patient group it was found that patients receiving sevelamer had unchanged median coronary artery and aorta calcification scores after 1 yr as opposed to Ca-treated patients whose arterial calcification scores increased 28% over baseline (12). Significantly, although both treatments controlled P levels equivalently, treatment with Ca containing binders led to an increased frequency of hypercalcemic episodes and greater suppression of serum parathyroid hormone (PTH) levels in hemodialysis patients (54,55).…”
Section: Can Vascular Calcification Be Controlled?mentioning
confidence: 99%